Characteristics of Endometriosis Patients in RSUP Dr. Kariadi Semarang in 2018 - Syarifah A Mansur; Yuli Trisetiyono; Muflihatul Muniroh; Nurul Setiyorini (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2022)
Background : Endometriosis is one of the gynecological disorders that affects women at reproductive age between 20-35 years. Based on the above, endometriosis can cause pain that can interfere daily activity and infertility.Aim : To found the incidence and characteristics of patients with endometriosis who undergoing treatment and surgery in RSUP Dr. Kariadi Semarang Method: This study was a descriptive study. Data retrieved from medical records of endometriosis’s patients who undergoing treatment and surgery at RSUP Dr. Kariadi Semarang 2018. The result presented in distribution and frequency characteristics tables.Result : The incidence of endometriosis in RSUP Dr. Kariadi Semarang in 2018 were 176 cases of 8690 inpatients in the obstetric and gynecology wards. Characteristics of endometriosis patients are most at the age of 20 - 35 years, nullipara, with complaints of menstrual pain / dysmenorrhoea, location in the ovary, by managing the surgery and using GnRH agonists, and not a recurrent endometriosis patient.Conclusion : The incidence of endometriosis in RSUP Dr. Kariadi Semarang 2018 was 176 cases of 8690 patients at the Obstetrics and Gynecology (2 %). Endometrosis highest incidence was in the reproductive age (20-35 years).